The Factors Which Influence Exclusive Breastfeeding Failure: Scoping Review - Yuliandary Yunus; Herlin Fitriana Kurniawati (International Journal of Advanced Science and Technology, 2020)
Exclusive breastfeeding provides long-term health benefits to mother and infant. Although the benefits of breastfeeding exclusively for maternal and infant health are many, but the prevalence of exclusive breastfeeding for 6 months around the world is less than 36%. This scoping review aims to gain evidence based of the factors affecting the failure of exclusive breastfeeding. This review used methodology for grouping review as Arksey and O’Malley suggested. The relevant articles were the publication of 2010-2019. 108 relevant articles filtered by abstrack, subject and outcome, obtained 9 articles. A review of this article explains there are two key factors that influence the failure of exclusive breastfeeding for 6 months, these are: (1) Socio-demographic factors such as: knowledge, education, and employment that each has an influence in the breastfeeding process, (2) Psychosocial factors such as breastfeeding intentions and family support for mothers who are breastfeeding. In conclusion, provider plays an important role in enhancing the success of exclusive breastfeeding apart from family support, husband and workplace, especially attributed to KIE given during the visit.